Producing Classics on outside Broadcast in the 1970s: The Little Minister (1975), As You Like It (1978) and Henry VIII (1979). Issue 3 (November 2015) - Smart, Billy
Cedric Messina, producer of Play of the Month (from 1967–77), the BBC Television Shakespeare (1978–80) and others, was responsible for the majority of BBC television adaptations of theatrical plays for over twenty years. This article examines three Messina Outside Broadcast (OB) productions, The Little Minister (1975), As You Like It (1978) and Henry VIII (1979), to explain the practice and significance of OB drama. Messina believed that recording in romantic real-life locations (castles, forests, stately homes) could inspire visual pleasure for viewers, an approach based upon the simultaneous, but perhaps contradictory, representation of the decorative/spectacular and the ('newsreel'/'documentary') real.